Adjuvant Technologies in the Construction of Advanced Vaccines - A. P. Semakova; N. I. Mikshis (Проблемы особо опасных инфекций, 2016)
Overarching objective of vaccinology is a search of new adjuvants, directly influencing immune-competent cells and stimulating expressed adaptive immune responses. Adjuvants have been used for the enhancement of immune response for over a hundred years. A considerable number of recent adjuvants capable not only to reinforce antigen intake by antigen-presenting cells (APC) or deliver it to the sites of immune-competent cell localization, but also acting as immediate immune activators, are at various stages of trials. When selecting an adjuvant a special attention should be given to the efficacy of immunological memory activation, capacity for complex Th1 and Th2 stimulation, provision for expressed immune response in the context of vaccine dose tapering and lowering of the frequency of administration, and innocuousness for the organism. Nowadays preference is set on the modifiers of functions and signaling pathways of innate immunity receptors.